Antesenden dan Konsekuensi Tax Avoidance dalam Laporan Keuangan Perusahaan - Neneng Sri Suprihatin (MEASUREMENT : Jurnal Program Studi Akuntansi, 2026)
This research aims to empirically test the influence of corporate social responsibility, capital intensity, and executive compensation on tax avoidance in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2016-2020. This research was conducted using associative quantitative methods. The research population was 54 companies, and a sample of 18 companies was taken using purposive sampling. The research was conducted at consumer goods sector companies on the IDX for 2016-2020. The type of data used is secondary data obtained from www.idx.co.id. Data was collected with the 2016-2020 annual report and analyzed with SPSS version 26. Tax avoidance in this research uses the Effective Tax Ratio (ETR) measurement. The results of hypothesis testing using t statistics show that corporate social responsibility affects tax avoidance. In contrast, capital intensity does not affect tax avoidance, and executive compensation affects tax avoidance. The test results show that corporate social responsibility, capital intensity, and executive compensation affect tax avoidance in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2016-2020.